Upper extremity and craniofacial vascularized composite allotransplantation: ethics and immunosuppression. Issue 6 (14th November 2019) - Benedict, James; Magill, Gerard
Abstract : Vascularized composite allotransplantation (VCA) is the name most often used to refer to the transplantation of anatomical units composed of multiple tissue types (skin, bone, muscle, tendon, nerves, vessels, etc.) when such transplants do not have the primary purpose of extending life, as is the case in the more familiar field of solid organ transplantation (SOT). A serious interest in VCA developed in the late twentieth century following advances in immunosuppression which had led to significant improvements in short and medium-term survival among SOT recipients. Several ethical concerns have been raised about VCA, with many being connected in one way or another to the limitations, burdens, and risks associated with immunosuppression. This article will focus on upper extremity and craniofacial VCA, beginning with a brief review of the history of VCA including reported outcomes, followed by a discussion of the range of ethical concerns, before exploring in greater detail how immunological issues inform and shape several of the ethical concerns.